Analysis of Organic Rice Supply Chain in Al-Barokah Farmers Association, Semarang District - Barki, Khotimatul; Dhita , Sylvia Gara; Nurohmiasih, Nia; Al-Amro, Imroatu Haiyin; Fimbriata, Fitrizka Acha (AgriDev, 2025)
Indonesia’s agriculture sector significantly contributes to national economic development, accounting for 13.28% of GDP in 2021. Rising demand for chemical free food has accelerated the growth of organic farming, particularly in organic rice cultivation; however, adoption remains limited. This study used a mixed methods approach on the Al-Barokah Farmers Association in Semarang, complemented by quantitative data from 100 respondents selected via purposive and snowball sampling, to examine challenges in market access, capital availability, and resource limitations. The Food Supply Chain Network (FSCN) model was used to analyze six key elements: supply chain targets, structure, management, resources, business processes, and performance. Results indicate that organic rice is distributed through five marketing channels, with the farmer’s share exceeding 50% across all channels, reaching up to 100% in some cases. The cooperative effectively maintains an efficient and interconnected supply chain, stabilizing prices and supporting export activities. The study recommends improving communication, optimizing marketing channel participation, and accurately calculating production costs to sustain the cooperative’s organic rice supply chain.